The Information on Exposure and Duration of Suffering with Medication Compliance in Patients of Hypertension - Susanto, Agus; Purwantiningrum, Heni; Muhamad Janadin Ass Saff, Muhamad (Window of Health : Jurnal Kesehatan, 2023)
The successfully of hypertension therapy is long-term blood pressure control. Taking antihypertensive drugs regularly is one way to control blood pressure. However, many hypertensive patients are reluctant to seek treatment and continue taking medication. Some factors associated with this condition are the length of time suffering from hypertension and exposure to information received. The use of drugs for a long time can trigger boredom, while credible information can increase adherence to therapy. This study aims to analyze the relationship between information exposure and duration of hypertension with medication adherence. The subjects of this study were hypertensive patients. The sample size was 320 people who suffered from hypertension for at least six months and were actively treated. The research data were collected with a questionnaire instrument and quota sampling technique. The data were processed with SPSS and presented univariately and bivariately. The correlation test used the Chi-Square test with a significance level of 0.05. The results showed that the majority of respondents were less compliant with taking medication. The correlation test of information exposure and duration of hypertension with medication adherence obtained a p-value of 0.000 for both variables. The test results indicate a relationship between information exposure and duration of hypertension with medication adherence. Hypertensive patients need to get credible information during their therapy. Therefore, it is very important to provide credible information facilities as a means to inform and educate hypertensive patients about the importance of medication adherence to optimize health status.